Visualizing the velocity fields and fluid behavior of a solution using artificial intelligence during EndoActivator activation - Harry Huiz Peeters; Elvira Theola Judith; Faber Yosua Silitonga; Lavi Rizki Zuhal (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Electrical devices driven sonically have been found in several studies to be effective to clean root canals but the effect of the EndoActivator irrigant activation flow behavior on cleaning efficacy is not completely understood. Purpose: The study aimed to provide an initial understanding of flow behavior and velocity field generation during the irrigant activation process by EndoActivator using artificial intelligence (AI). Methods: A straight glass model was filled with a solution containing 17% EDTA. Meanwhile, a medium activator tip with 22-mm polymer noncutting #25, 0.04 file driven by an electrical sonic hand-piece at 190 Hz (highest level) was used to induce velocity field to produce micro-bubbles. The physical mechanisms involved were recorded using a Miro 320S highspeed imaging system, the hydrodynamic responses were recorded, and analyzed using a motion estimation program supported by LiteFlowNet (AI). Results: The rapid fluid flow was visualized clearly in the model when it was activated by an EndoActivator tip. It was also observed that the distal end of the EndoActivator tip generated a near-wall high gradient velocity apically in all directions of the oscillation. Conclusion: The analysis showed that the proposed motion estimation program, supported by LiteFlowNet (AI), was able to capture velocity magnitude estimation of a non-PIV experiment and visualize the bubbles generated in the solution.